Emerging Use of Public-Private Partnerships in Public Radiotherapy Facilities in Nigeria. (2021) - Anakwenze Akinfenwa, Chidinma P.; Ibraheem, Abiola; Nwankwo, Kenneth; Lasebikan, Nwamaka; Ali-Gombe, Musa; Aliyu, Usman Malami; Ikhile, Emmanuel; Adegboyega, Omobolanle; Abdullahi, Adamu; Klopp, Ann H.; Schmeler, Kathleen; Lin, Lilie L.; et al.
Abstract : PURPOSE: Radiotherapy (RT) treatment at public hospitals in Nigeria is often interrupted by prolonged periods of machine breakdown because of insufficient funds for maintenance and repair. These delays have prompted the uptake of public-private partnerships (PPPs) to acquire and maintain RT equipment. This study aimed to understand Nigeria's current RT capacity and the impact of PPPs on RT availability and cost. METHODS: Eleven radiation oncologists, each representing one of the 11 RT centers in Nigeria (eight public and three private), were invited to complete a survey on the type, status, acquisition, and maintenance plan of existing RT equipment, cost incurred by patients for external-beam radiation (EBRT) and brachytherapy treatment, and number of patients treated per year on each machine. Type and status of equipment at nonresponding facilities were obtained through literature review and confirmed with the facility. RESULTS: A total of eight (81%) respondents completed the survey, all representing public centers, three of which reported PPP use. They reported 11 megavoltage units in total (seven linear accelerators [LINACs] and four Cobalt-60s) and 10 brachytherapy afterloaders. Of those, 57% (4/7) of the LINACs, 100% (4/4) of the Cobalt-60s, and 63% (7/11) of the afterloaders were in clinical use. All commissioned equipment supported by PPPs (three LINACs and one afterloader) were in operation. The public EBRT equipment were nonfunctional 35% of the year (resulting in 60% fewer patients treated per year). The PPP EBRT and afterloaders did not experience any periods of breakdown, but PPP costs were 338% higher than public equipment. CONCLUSION: This study characterizes the use of PPP as a more reliable method of RT delivery in Nigeria, albeit at higher costs.